The absorption enhancement of norisoboldine in the duodenum of adjuvant‐induced arthritis rats involves the impairment of P‐glycoprotein. (January 2017) - Duan, Cong; Guo, Jiao‐Mei; Dai, Yue; Xia, Yu‐Feng
Abstract: Lindera aggregata (Sims) Kosterm root has been used in traditional Chinese medicine for the treatment of rheumatism palsy, dyspepsia and frequent urination for a long time. Norisoboldine, the main active constituent of this herb drug, possesses outstanding anti‐arthritis activity. However, the in vivo disposition of norisoboldine is known to a limited extent, especially under the pathological condition of rheumatoid arthritis (RA). The aim of this study is to investigate whether and how the absorption of norisoboldine is altered in adjuvant‐induced arthritis (AIA) rats. Comparative studies of the intestinal absorption of norisoboldine in normal and AIA rats at different pathological stages of the arthritis were performed using in situ single‐pass intestinal perfusion, and the effects of an inhibitor of efflux proteins were also investigated. Norisoboldine was shown to be a substrate of P‐glycoprotein (P‐gp), as P‐gp inhibitor verapamil markedly increased the permeability coefficient ( P eff ) of norisoboldine by 88% in the intestine of normal rats. Compared with normal rats, AIA rats displayed increased P eff values of norisoboldine by 84% and 86% on day 5 and day 10 after the appearance of the secondary response of arthritis, respectively. Verapamil could eliminate the difference of intestinal absorption of norisoboldine between normal and AIA rats. Further studies showed that impaired expression and activity of P‐gp in AIA rats play a decisive role in the absorption enhancement of norisoboldine. Notably, the impairment of P‐gp function positively correlated with the severity of arthritis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Norisoboldine showed increased absorption in the intestines of AIA rats possibly by down‐regulating the expression and activity of P‐gp.